A landscape-based analysis of fixed temperature and simulated annealing - Franzin, Alberto; Stützle, Thomas (European journal of operational research, 2023)
•We extensively compare two variants of simulated annealing on different problems.•We automatically generate optimized versions of each algorithm for various scenarios.•We propose new features to study the behaviour of stochastic local search algorithms.•The behaviour of an optimal algorithm is related to the landscape it encounters. Since the introduction of Simulated Annealing (SA), researchers have considered variants that keep the same temperature value throughout the whole search and tried to determine whether this strategy can be more effective than the original cooling scheme. Several studied have tried to answer this question without a conclusive answer and without providing indications that could be useful for a practical implementation. In this work, we address this question following an experimental approach, relating the characteristics of the algorithms with the characteristics of the landscapes they encounter. We use problem-independent landscape features to study the algorithmic behaviour across different problems. We consider three different objective functions and various instance classes and determine the conditions under which the fixed-temperature variant of SA can outperform its original counterpart and when SA is instead a better choice.